The effects of chronic alcoholism on cell proliferation in the human brain - Sutherland, G.T.; Sheahan, P.J.; Matthews, J.; Dennis, C.V.P.; Sheedy, D.S.; McCrossin, T.; Curtis, M.A.; Kril, J.J. (Experimental neurology, 2013)
Neurogenesis continues in the human subventricular zone and to a lesser extent in the hippocampal subgranular zone throughout life. Subventricular zone-derived neuroblasts migrate to the olfactory bulb where survivors become integrated as interneurons and are postulated to contribute to odor discrimination. Adult neurogenesis is dysregulated in many neurological, neurovascular and neurodegenerative diseases. Alcohol abuse can result in a neurodegenerative condition called alcohol-related brain damage. Alcohol-related brain damage manifests clinically as cognitive dysfunction and the loss of smell sensation (hyposmia) and pathologically as generalized white matter atrophy and focal neuronal loss. The exact mechanism linking chronic alcohol intoxication with alcohol-related brain damage remains largely unknown but rodent models suggest that decreased neurogenesis is an important component. We investigated this idea by comparing proliferative events in the subventricular zone and olfactory bulb of a well-characterized cohort of 15 chronic alcoholics and 16 age-matched controls. In contrast to the findings in animal models there was no difference in the number of proliferative cell nuclear antigen-positive cells in the subventricular zone of alcoholics (mean±SD=28.7±20.0) and controls (27.6±18.9, p=1.0). There were also no differences in either the total (p=0.89) or proliferative cells (p=0.98) in the granular cell layer of the olfactory bulb. Our findings show that chronic alcohol consumption does not affect cell proliferation in the human SVZ or olfactory bulb. In fact only microglial proliferation could be demonstrated in the latter. Therefore neurogenic deficits are unlikely to contribute to hyposmia in chronic alcoholics. •Animal studies show that alcohol decreases adult neurogenesis.•This effect has never been investigated in human brain tissue.•We compared cell proliferation in the olfactory system of alcoholics and controls.•In contrast to animal models there were no differences seen in alcoholics.•Alcohol-related brain damage is unlikely to involve perturbed neurogenesis.